Suicides in adolescence: A twelve-year study from Eastern Turkey - Kafadar, Huseyin; Kafadar, Safiye; Tokdemir, Mehmet (Elsevier Sci Ltd, 2014)
Suicide is a form of behavior brought about by a combination of biological, psychological, and social factors and the adverse effects of those factors on individuals, their surroundings, society, and subsequent generations. In this study, attention is focused on the increase in adolescent suicides in Elazig and the surrounding province. The probable suicide cases among adolescent deaths that occurred in Eastern Turkey between 2001 and 2012 were examined retrospectively. A total of 67 cases were evaluated in terms of age, sex, method of death, death location, and the time of the year at which death occurred. Of the 67 study cases, 40 were female (59.70%) and 27 were male (40.29%). When the methods of suicide were analyzed, it was found that hanging came in first place with 34 cases (50.74%), followed by death using a firearm with 27 cases (40.29%). Other types of death were self-poisoning in four cases (5.97%) and jumping from a height in two cases (2.98%). According to this study, there are common risk factors both for suicidal thoughts and suicide attempts. Defining the prevalence of suicidal thoughts leading to suicide attempts, determining the risk factors, and evaluating the relationship between those factors and mental disorders will enable society to develop new approaches to suicidal behavior. (C) 2014 Elsevier Ltd and Faculty of Forensic and Legal Medicine. All rights reserved.
Keywords: Suicide; Suicide attempts; Adolescent